Romania : Second Review under the Stand-By Arrangement and Request for Modification of Performance Criteria-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report, 2011)
Although the economic growth of Romania has resumed, it has boosted downside risks. However, the country has continued its strong performance under the new program in strengthening macroeconomic policies, accelerating structural reforms, and consolidating economic development. In conclusion, the authorities concur that the current precautionary Stand-By Arrangement (SBA) will provide additional security against unforeseen shocks, thereby setting the stage for strong and sustainable economic development while maintaining external and internal stability and thereby achieving the fiscal goals for 2012.